Newborn Septic Arthritis-A Rare Presentation of Late-Onset Group B Streptococcal Disease: Case Report and Short Review of the Literature - Rahel Schuler; Harald Ehrhardt; Klaus-Peter Zimmer; Daniel Berthold; Janina Trauth; Christian Fölsch; Markus Waitz (Thieme Medical Publishers, Inc., 2021)
Group B Streptococcus (GBS) disease is a leading cause of invasive bacterial infections among neonates. We present the case of an 11-day-old neonate with septic arthritis as a rare presentation of late-onset disease (LOD) with a favorable short-term outcome. GBS is a leading cause of neonatal infection. Early-onset disease (EOD) is defined as infection from birth to 6 days of age, while LOD occurs from 7 days to approximately 3 months of age. EOD is acquired through vertical transmission and can be reduced through application of intrapartum antibiotic prophylaxis (IAP). LOD can be acquired from the mother or from environmental sources, unlikely to be prevented by IAP. The most common presentation of EOD is bacteremia (83%), pneumonia (9%), and meningitis (7%). While the clinical picture in both EOD and LOD frequently resembles in LOD hamatogenous spreading may predispose neonates to present with uncommon organ manifestation other than the classic systemic signs of sepsis, for example, septic arthritis. Herein, we report on the management and outcome of a term neonate with late onset GqBS bacteremia and subtle clinical symptoms of septic monoarthritis.